2011
DOI: 10.1111/j.1462-2920.2011.02523.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects on survival and performance of Norway spruce seedlings colonized by dark septate root endophytes are primarily isolate‐dependent

Abstract: Root endophytes are common and genetically highly diverse suggesting important ecological roles. Yet, relative to above-ground endophytes, little is known about them. Dark septate endophytic fungi of the Phialocephala fortinii s.l.-Acephala applanata species complex (PAC) are ubiquitous root colonizers of conifers and Ericaceae, but their ecological function is largely unknown. Responses of Norway spruce seedlings of two seed provenances to inoculations with isolates of four PAC species were studied in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 72 publications
7
80
3
1
Order By: Relevance
“…The ecology of dark septate endophytes is relatively less well known than that of other rootassociated fungi. The effects of DSEs on spruce range from neutral to negative and are straindependent (Tellenbach et al, 2011;Reininger et al, 2012). The relative increase in dark septate endophytes 1 year after the tree dieback may indicate their use of dead spruce roots as a substrate for growth.…”
Section: Discussionmentioning
confidence: 99%
“…The ecology of dark septate endophytes is relatively less well known than that of other rootassociated fungi. The effects of DSEs on spruce range from neutral to negative and are straindependent (Tellenbach et al, 2011;Reininger et al, 2012). The relative increase in dark septate endophytes 1 year after the tree dieback may indicate their use of dead spruce roots as a substrate for growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although many DSE fungi form similar morphological structures in the host roots (Jumpponen & Trappe 1998, Rodriguez et al 2009), they are taxonomically unrelated, vary in ecological or physiological functions and lead to variable host responses (Addy, Piercey & Currah 2005, Alberton, Kuyper & Summerbell 2010, Newsham 2011, Tellenbach, Grünig & Sieber 2011, Knapp, Pintye & Kovacs 2012. Our earlier studies in the tallgrass prairie concluded that while grasses overall tend to be colonized to a greater extent and respond more positively to DSE colonization, forbs also range from increased to no response to decreased biomass accumulation in their response to DSE fungi (Mandyam, Fox & Jumpponen 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of the symbioses may be influenced by the variability of component fungi (Munkvold et al 2004, Koch, Croll & Sanders 2006, Mandyam et al 2012, Tellenbach et al 2011 or host plants (Jones, Durall & Tinker 1990, Thomson et al 1994, Karst, Jones & Turkington 2009, Hoeksema et al 2010, as well as by abiotic variability in the availability of light or nutrients or in the stress under which the host-fungus symbiosis is evaluated (Johnson et al 1997, Redman, Dunigan & Rodrigues 2001, Rodriguez et al 2008, Johnson et al 2010, Newsham 2011. Compared to better known mycorrhizal symbioses or the vertically transmitted systemic foliar endophytes, the root-associated fungal endophytes have received little attention (Rodriguez et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In arid grasslands, fungal communities in grass rhizospheres are dominated by dark septate endophytes, a polyphyletic group characterized by melanized, septate hyphae [27,28]. They may facilitate host water uptake, increase plant acquisition of organic nitrogen [29,30] or act as plant pathogens [31]. Arbuscular mycorrhizal fungi (AMF) also colonize grass roots at the Sevilleta [32].…”
Section: Methods and Materials (A) Study Systemmentioning
confidence: 99%